Narrative Review: Herbal Nanocosmetics for Anti Aging - Prilyano Garcella; Triyadi Hendra Wijaya; Dhadhang Wahyu Kurniawan (Universitas Sebelas Maret, 2023)
Skin aging is a complex biological process caused by intrinsic and extrinsic factors. There are various approaches to preventing skin aging, one of which is using herbal nanocosmetics. This narrative review aims to determine the natural ingredients, type of nanoformulations, and its effects of herbal nanocosmetics to prevent skin aging. The method used in this study was searching for articles related to herbal nanocosmetics to avoid aging skin through Google Scholar, PubMed, and Science Direct with the keywords herbal plants, anti-aging, herbal cosmetics, cosmetics, nanocosmetics, nanoformulations, nanoparticles, nanomaterials, and topical delivery. The inclusion criteria were research articles or review articles about herbal plants made into herbal nanocosmetics to prevent skin aging with the topical route of administration published between 2010-2021 in full text. The articles that have been obtained are then selected, reviewed, and analyzed. Herbal plants made into herbal nanocosmetics contain phenolic compounds for nanoformulations used, namely silver nanoparticles, solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLC), nanoemulsions, liposomes, niosomes, ethosomes, and transfersomes. These nanocosmetics herbs affect skin aging, including UV protection, preventing wrinkles and dark spots, moisturizing and brightening the skin. The herbal nanocosmetics prevent the effects of skin aging through some mechanisms such as anti-oxidant, photoprotective agents, modulators of collagen or elastin synthesis, and inhibitors of melanin synthesis.